2017
DOI: 10.1371/journal.pone.0185526
|View full text |Cite
|
Sign up to set email alerts
|

HIV and tuberculosis co-infection among migrants in Europe: A systematic review on the prevalence, incidence and mortality

Abstract: BackgroundInternational human migration has been rapidly growing. Migrants coming from low and middle income countries continue to be considerably vulnerable and at higher risk for infectious diseases, namely HIV (Human Immunodeficiency Virus) and tuberculosis (TB). In Europe, the number of patients with HIV-TB co-infection has been increasing and migration could be one of the potential driving forces.ObjectiveThis systematic review aims to improve the understanding on the burden of HIV-TB co-infection among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 42 publications
3
38
1
3
Order By: Relevance
“…A systematic review on the prevalence, incidence and mortality of HIV-TB co-infection in Europe observed a disproportionate vulnerability of migrants to co-infection across studies 134 . Given that only 3.8% of TB cases in England in 2015 involved co-infection with HIV 14 , TB-HIV co-infection cannot be considered a major driver of higher TB incidence among migrants and ethnic minorities in the UK; although this group represents an important target in the prevention of M.tb infection and progression to active disease.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…A systematic review on the prevalence, incidence and mortality of HIV-TB co-infection in Europe observed a disproportionate vulnerability of migrants to co-infection across studies 134 . Given that only 3.8% of TB cases in England in 2015 involved co-infection with HIV 14 , TB-HIV co-infection cannot be considered a major driver of higher TB incidence among migrants and ethnic minorities in the UK; although this group represents an important target in the prevention of M.tb infection and progression to active disease.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…Extrapulmonale Tuberkulosen bei HIV-Patienten sind häufiger (▶ Abb. 7), ebenso Therapieversagen und eine multiresistente Tuberkulose [27].…”
Section: Hiv-infektionunclassified
“…Domestic migrants in China regularly move from rural areas to host cities for work without permanent residency (Hukou) (Huinink et al, 2014). Large studies have shown that these migrants are more vulnerable to TB infection than local people and have become a contributor to TB epidemics (Tavares et al, 2017). Again, reasons for this are reportedly due to a lack of TB awareness when compared with local residents (Pengpid et al, 2016;Nkulu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%